2020
DOI: 10.2217/imt-2020-0256
|View full text |Cite
|
Sign up to set email alerts
|

Pasotuxizumab, a Bite ® Immune Therapy for Castration-Resistant Prostate Cancer: Phase I, Dose-Escalation Study Findings

Abstract: Aim: We report results of a first-in-human study of pasotuxizumab, a PSMA bispecific T-cell engager (BiTE®) immune therapy mediating T-cell killing of tumor cells in patients with advanced castration-resistant prostate cancer. Patients & methods: We assessed once-daily subcutaneous (SC) pasotuxizumab. All SC patients developed antidrug antibodies; therefore, continuous intravenous (cIV) infusion was assessed. Results: A total of 47 patients received pasotuxizumab (SC: n = 31, 0.5–172 μg/d; cIV: n = 16, 5–8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 36 publications
1
73
0
3
Order By: Relevance
“…Accordingly, in the last decade, several studies reported on this and other PSMA targeting radiolabeled agents that showed clinical activity in CRPC [ 57 , 58 , 59 , 60 ]. In line, a plethora of preclinically characterized therapeutic constructs and almost all bsAbs that underwent clinical evaluation in PC are directed to PSMA [ 61 , 62 , 63 , 64 ].…”
Section: Bsabs In Prostate Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…Accordingly, in the last decade, several studies reported on this and other PSMA targeting radiolabeled agents that showed clinical activity in CRPC [ 57 , 58 , 59 , 60 ]. In line, a plethora of preclinically characterized therapeutic constructs and almost all bsAbs that underwent clinical evaluation in PC are directed to PSMA [ 61 , 62 , 63 , 64 ].…”
Section: Bsabs In Prostate Cancermentioning
confidence: 99%
“…Another major drawback of some bsAb constructs is the occurrence of anti-drug antibodies (ADAs) [ 61 , 92 , 93 ], which may not only limit efficacy, but can also cause side effects.…”
Section: Toxicity Considerationsmentioning
confidence: 99%
See 3 more Smart Citations